Strategy for the Development of Kampung Sasirangan as Edutourism Village - Nasruddin Nasruddin; Ellyn Normelani; Rosalina Kumalawati (Program Pascasarjana, 2019)
Kampung Sasirangan is one of the centers of traditional textile production of Banjarese called Sasirangan in South Kalimantan. Sasirangan was produced by the local community in the home industry scale with traditional process and production. The aim of the research is to identify and develop strategy to develop Kampung Sasirangan as an edutourism destination. The methods consist of direct observation in the home industry of Sasirangan traditional textile, in-depthÂ interview, literature study, and focus group discussion. Research result shows that strategy to create edutourism sites of Sasirangan textile should include local community and local government participation. The Sasirangan product should be able to create a competitive product, reasonable prices, and high quality of the textile product. To provide edutourism attraction for educational purposes, it is important to provide a program for tourist to directly observe the traditional process to make Sasirangan. A guide from local people or craftsmen was important to ensure the interpretation of the traditional process was delivered properly. In such a case, the community development is crucial. The local government should be able to promote community development program through the establishment of a community group which is work in edutourism in the village. There also important to provide training, working capital, production tools, and assistance in promotion and marketing.Keywords: Edutourism, traditional textile, Sasirangan.